PENGARUH EARNING PER SHARE DAN DIVIDEND PAYOUT RATIO TERHADAP HARGA SAHAM (STUDI EMPIRIS PADA PERUSAHAAN BISNIS 27 YANG TERDAFTAR DI BEI PERIODE 2020-2022) - Nitasari Eka Puspita Ningrum; Yenny Ernitawati; Roni Roni (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Declining financial performance has a direct impact on a company's stock price, primarily due to decreases in revenue and net income, which lead to a decline in Earnings per Share (EPS). This reduces investor interest in investing, while a lack of transparency and accountability in corporate governance further diminishes investor confidence, ultimately negatively affecting stock prices. This study aims to analyze the effect of Earnings Per Share (EPS) and Dividend Payout Ratio (DPR) on stock prices in 27 companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. The study employs a quantitative research method using a multiple linear regression approach. The data used are annual financial reports of the companies, downloaded from the Indonesia Stock Exchange website. The results show that EPS has a positive and significant effect on stock prices, with a t-value of 3.488, greater than the t-table value of 1.664, and a significance value of 0.001 < 0.05. Conversely, DPR does not significantly affect stock prices, with a t-value of 0.107, smaller than the t-table value of 1.664, and a significance value of 0.915 > 0.05. Simultaneously, EPS and DPR were found to have a significant effect on stock prices, with an F-value of 6.318, greater than the F-table value of 3.959. These findings conclude that EPS is a more important factor in influencing stock prices compared to DPR in the companies analyzed. The implications of this study suggest that investors should consider EPS and DPR as key factors in fundamental analysis before making investment decisions in companies listed on the IDX.